Modelling Adaptation to Climate Change in Agriculture - Ignaciuk A; Mason-D'Croz, Daniel (Organization for Economic Cooperation and Development, 2014)
This paper investigates how climate change can affect agricultural production and proposes some adaptation measures that could be undertaken to mitigate the negative effects of climate change while enhancing the positive ones. The paper stresses the importance of planned adaptation measures and highlights possible strategies for reducing risk and improving resilience. To quantify the possible effects of climate change and the effects of adaptation measures this study uses the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT). The analysis first explores the potential effects of climate change on yields and prices. It then goes on to analyse the potential impacts of two distinctive sets of adaptation strategies on yields, prices, and food security, namely: i) research and development (to develop new crop varieties that are better suited to changed climate conditions) and ii) changes in irrigation technology. Last, the analysis in this paper estimates the public and private investment needs in research and development (R&D) for developing new crop varieties, and further develops estimates of the cost of improving irrigation technologies in OECD countries.